The use of melatonin for treating sleep disorders in patients with Parkinson’s disease - Srinivasan, Venkataramanujam; Berardis, Domenico De; Partonen, Timo; Zakaria, Rahimah; Othman, Zahiruddin (Dove Medical Press, 2014)
Most patients with Parkinson’s disease (PD) experience sleep-related problems, such as difficulty in initiating and maintaining sleep, excessive daytime sleepiness, sleep fragmentation, reductions in non-rapid eye movement (NREM) or rapid eye movement (REM) sleep, and REM sleep behavior disorder. Although motor symptoms of PD are treated with dopaminergic drugs, the nonmotor symptoms pose a big problem, and they often precede the onset of the disease. Treating the nonmotor symptoms, such as sleep and associated behavioral disorders, is beneficial, for it not only relieves the symptoms but also helps to slow the progression of the disease. Treating PD patients with melatonin has been shown to be beneficial in treating sleep and behavior problems. The finding of reduced expression of the MT1 and MT2 melatonin receptors in amygdalae and substantia nigra of PD patients supports the involvement of melatonergic system in the etiology of PD. Hence, the use of melatonin or its analogs may even be beneficial not only for improving sleep quality but also for enhancing neuroprotection in PD.